2017
DOI: 10.1155/2017/3279821
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Overnight Orthokeratology on Corneal Surface Shape and Optical Quality

Abstract: Purpose To investigate the changes of corneal surface shape and optical quality during orthokeratology. Methods 49 eyes of 26 patients (10.63 ± 2.02 years old) who underwent overnight orthokeratology for myopia were prospectively examined. The corneal surface shape parameters, including surface regularity index (SRI) and surface asymmetry index (SAI), were attained with an OPD-III SCAN. The higher-order aberrations and higher-order Strehl ratios were calculated under a 3 mm pupil diameter before orthokeratolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…The sample size was calculated with G*Power (version 3.1.9.2; Kiel University, Kiel, Germany) based on the average apical corneal power difference anticipated between the two eyes during orthokeratology treatment. A minimum interocular difference of 0.50 D was expected with a within-subject standard deviation of 0.70 D. 18 Therefore, a minimum of 18 subjects were required to provide 80 per cent power to detect a significant difference with an alpha level of 0.05.…”
Section: Sample Size Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample size was calculated with G*Power (version 3.1.9.2; Kiel University, Kiel, Germany) based on the average apical corneal power difference anticipated between the two eyes during orthokeratology treatment. A minimum interocular difference of 0.50 D was expected with a within-subject standard deviation of 0.70 D. 18 Therefore, a minimum of 18 subjects were required to provide 80 per cent power to detect a significant difference with an alpha level of 0.05.…”
Section: Sample Size Determinationmentioning
confidence: 99%
“…As the corneal shape is altered during orthokeratology treatment, both corneal and ocular aberrations, primarily spherical and comatic aberrations, significantly increase . Hiraoka et al investigated the correlations between ocular aberrations and axial elongation in 55 children (mean age: 10.3 ± 1.4 years) undergoing orthokeratology treatment for one year and showed that children with greater increases in the root‐mean‐square (RMS) error values for spherical, comatic, and total higher‐order aberrations (HOAs) exhibited slower axial eye growth.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Sun et al have recently reported increased corneal irregularity and ocular HOA (spherical aberrations and comas) with OK lenses, despite improvements in refractive error. [24] No significant lens decentration was seen in our patients.…”
Section: Discussionmentioning
confidence: 42%
“…Regarding OK, the change in corneal geometry causes an increase in ocular aberrations [64,65]. Chen et al [61] described a statistically significant rise in spherical aberrations (0.05 ± 0.6 to 0.19 ± 0.13 µm) and coma aberrations (0.12 ± 0.19 to 0.36 ± 0.23 µm).…”
Section: Orthokeratologymentioning
confidence: 99%